AKSENTUASI BIBLIOTHERAPY DI PERPUSTAKAAN PERGURUAN TINGGI - Saleha Rodiah (Universitas Padjadjaran, 2013)
College libraries in helping to educate the nation in all aspects of life can play an active role in serving pemustakanya, in this case the student through bibliotherapy activities or therapy literature. Bibliotheraphy an old concept of librarianship. Bibliotherapy services performed in high library implemented to help problem students the nature of academic and non-academic, suspected to disrupt the continuity of studies, with facilitators trained librarians as biblioterapis. Bibliotherapy activities can be applied in the college library with attention to aspects that support the implementation of effective bibliothetrapy. Perpustakaan perguruan tinggi dalam membantu mencerdaskan bangsa dalam segala aspek kehidupan dapat berperan aktif dalam melayani pemustakanya, dalam hal ini mahasiswa melalui kegiatan bibliotherapy atau terapi pustaka. Bibliotheraphy merupakan konsep lama kepustakawanan. Layanan bibliotherapy dilakukan di perpustakaan tinggi dilaksanakan untuk membantu masalah mahasiswa yang bersifat akademik maupun non akademik yang ditengarai dapat mengganggu kelangsungan studinya, dengan fasilitator pustakawan terlatih sebagai biblioterapis. Kegiatan bibliotherapy dapat diterapkan di perpustakaan perguruan tinggi dengan memperhatikan aspek-aspek yang mendukung terselenggaranya bibliothetrapy secara efektif.